Analisis Minat dan motivasi Belajar, Pemahaman Konsep dan Kreativitas Siswa terhadap hasil Belajar Siswa dalam Materi Geometri Selama Pembelajaran Dalam Jaringan kelas X SMA Kota Medan - Susi Sihombing (Sepren, 2021)
This research is an ex-post facto research which is correlative in nature. The problems investigated in this study are the relationship between interest and creativity variables, conceptual understanding, motivation to mathematics learning outcomes. Data collected were processed using statistical analysis "SPSS and Minitab". The analysis showed that the interest in learning mathematics obtained an average score of 76.84 from a maximum value of 100 with a standard deviation of 7.8 and a variance of 61.67. Furthermore, testing the hypothesis using multiple linear regression analysis, it is concluded that (1) interest in learning mathematics has an influence on the learning outcomes of class students (2) creativity in learning mathematics does not have an effect on the learning outcomes of class students (3) motivation to learn mathematics has an effect on the results. Students 'learning mathematics (4) Understanding the concept of learning mathematics has an influence on students' mathematics learning outcomes.